Sedentary behaviors and emerging cardiometabolic biomarkers in adolescents - Martinez-Gomez, D.; Eisenmann, J.; Healy, Genevieve; Gomez-Martinez, S.; Diaz, L.; Dunstan, D.; Veiga, O.; Marcos, A. (2012)
Objective: To examine the associations of objectively measured sedentary time and television (TV) viewing time with emerging inflammatory and endothelial function markers in adolescents. Study design: This study comprised 183 adolescents (88 girls), aged 13 to 17 years. Sedentary time and moderate-to-vigorous physical activity was objectively measured with accelerometry, whereas TV viewing time was self-reported. White blood cell counts and levels of C-reactive protein, complement factors C3 and C4, interleukin-6, adiponectin, leptin, intercellular adhesion molecule 1, vascular cell adhesion molecule 1, E-selectin, L-selectin, and plasminogen activator inhibitor-1 were measured in fasted blood samples. Results: Sedentary time was not significantly associated with any of the examined cardiometabolic markers after controlling for potential confounders. However, TV viewing time was positively associated with soluble endothelial adhesion molecules intercellular adhesion molecule 1 (standardized ß = 0.19, P =.008), vascular cell adhesion molecule 1 (ß = 0.17, P =.020), L-selectin (ß = 0.18, P =.013), and E-selectin (ß = 0.16, P =.023) concentrations, after controlling for sex, age, pubertal status, moderate-to-vigorous physical activity, body mass index, and total sedentary time. Conclusions: High TV viewing time may play a key role in cardiovascular and metabolic diseases through the cell adhesion molecules in adolescence. Copyright © 2012 Mosby Inc. All rights reserved.